Crystallization kinetics of Ge₂₂Sb₂₂Tе₅₆ doped with Se and Ni - Garsia-Garsia, E.; Yanez-Limon, M.; Vorobiev, Y.; Espinoza-Beltran, F.; Gonzalez-Hernandez, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
Effects of Ni and Se incorporation on the crystallization kinetics of Ge:Sb:Te alloys have been studied. Both elements were found to increase the stability of the amorphous structure. The kinetics of crystallization under isothermal treatments indicates that Ni reduces both the barrier for thermal crystallization and the crystallization rate. Crystallization of samples containing Se is also retarded, possibly due to a stronger bonding of this element in comparison with Te.